2010
DOI: 10.1111/j.1749-6632.2010.05875.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines as novel biomarkers and regulators of the metabolic syndrome

Abstract: Over the past two decades our view of adipose tissue has undergone a dramatic change from an inert energy storage tissue to an active endocrine organ. Adipose tissue communicates with other central and peripheral organs by synthesis and secretion of a host of molecules that we generally refer to as adipokines. The levels of some adipokines correlate with specific metabolic states and have the potential to impact directly upon the metabolic homeostasis of the system. A dysregulation of adipokines has been impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
364
3
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(396 citation statements)
references
References 215 publications
4
364
3
25
Order By: Relevance
“…The mechanism by which adiponectin affects glucose tolerance is not yet fully understood but it has been attributed to its insulin-sensitizing and anti-inflammatory properties [4,5]. A decrease in adiponectin is believed to precede the onset of insulin resistance [4], but this has not yet been proven and has also been questioned [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which adiponectin affects glucose tolerance is not yet fully understood but it has been attributed to its insulin-sensitizing and anti-inflammatory properties [4,5]. A decrease in adiponectin is believed to precede the onset of insulin resistance [4], but this has not yet been proven and has also been questioned [28].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in adiponectin is believed to precede the onset of insulin resistance [4], but this has not yet been proven and has also been questioned [28]. It remains unclear whether adiponectin has a causal effect on diabetes or is simply acting as a surrogate marker for some other metabolic risk factor(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even moderate weight loss of about 10% or less has been shown to contribute to several health benefits including improved metabolic parameters, reduced blood pressure, and increased longevity [ Adipose tissue is an endocrine organ with a large and biologically active secretome [180] [181] and fat tissue in obese individuals is characterized by increased expression and / or secretion of several pro-inflammatory cytokines. as well as adipokine to promote inflammation, atherogenesis and insulin resistance, while the biosynthesis of anti-inflammatory, antiatherogenic and insulin-sensitizing adipokines such as adiponectin decreases [182] [183] Several studies have shown an increase in circulating levels of leptin and an increase in adiposity associated with leptin resistance and that this condition may contribute to the onset and / or maintenance of obesity [184]. ]…”
Section: Iii-2-5 Obesitymentioning
confidence: 99%
“…Adipokines that are produced by adipose tissue have extensive effects on carbohydrate and lipid metabolism and also in the pathogenesis of MetS (5). A characteristic imbalance of adipokine profile has been observed in obese subjects and/or those with MetS (6). Omentin as a new adipokine is encoded by two genes (1 and 2).…”
Section: Introductionmentioning
confidence: 99%